Effect of agility in different dimensions of manufacturing systems: A review. (2022) - Sharma, Sameer; Oberoi, Jaspreet Singh; Gupta, Rahul Dev; Saini, Sanjeev; Gupta, Arun Kumar; Sharma, Neeraj
Abstract: In this paper, an organized attempt has been made to describe in brief different information described in the investigation of the literature on the various facets of agility in the manufacturing system and demonstrate its interaction with different organization capabilities in manufacturing organizations. A methodical review on the concept, phraseology, and related facets of various organization capabilities and agility has also been included. Also, various methodologies that will be utilized in this research are reviewed in the literature. The literature has been reviewed on the agility concept. Different agility aspects, dimensions, nature, and terminology are covered in the literature review. Different types of organizational capabilities have been discussed and the organization capability dimensions required to achieve agility in the manufacturing system have been identified. Finally, various barriers to achieving agility have been reported and discussed. To the best knowledge of authors, this work is the improved attempt to hire and study the past and present level of agility in manufacturing systems. The findings of this study will support academics and executives in AM implementation in a smoother and effective way in manufacturing industries.